The Menghidupkan Kembali Spirit Politik Ilmu Pemerintahan - Mohamad Firdaus (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2020)
Government science is basically the study of political science, where in how many aspects of government science such as methods and methodology are not much different from political science. This paper tries to explain and describe the relationship between government science and political science. So far, the science of government has only studied bureaucracy, public administration, management and public policy. By only understanding it as a science of administration, government science becomes only like office science. This is due to the colonial heritage and the proliferation of neoliberalism. For this reason, this paper will try to bring the spirit of political science into government science which will explain that in reality, aspects of government are strongly influenced by political aspects. And provide a new alternative to the existence of governmental science based on glorifying the people.